Nécropole et bourgade d’artisans : l’évolution des sites de Bobigny (Seine-Saint-Denis), entre La Tène B et La Tène D - Stéphane Marion; Yves Le Bechennec; Cyrille Le Forestier (Revue Archéologique du Centre de la France)
This article shows the main results obtained from the necropolis and the grouped habitat of Bobigny. The site was studied through various unlinked excavations of variable size. The evolution of the occupation of every area is shown in a succinct way. A comparison of the data reveals that the habitat developed in most cases from La Tène C2. From the beginning of this period it covered a vast area and resembles a habitat put together for craft purposes. In the course of Tène B2 and C1, this village was preceded by the establishment of a very vast necropolis which gathered more than 500 individuals and in which, as much from a demographic point of view (children, women, men) as from a social point of view (modest tombs, finery, weaponry), a broad part of the population seems represented.